2016
DOI: 10.1016/j.jaci.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Exome and genome sequencing for inborn errors of immunity

Abstract: The advent of next generation sequencing (NGS) in 2010 has transformed medicine and particularly the growing field of monogenic inborn errors of immunity, including primary immunodeficiencies (PID). NGS has facilitated the discovery of novel disease-causing genes and the genetic diagnosis of patients with PID. Whole-exome sequencing (WES) is presently the most cost-effective approach for PID research and diagnostics, though whole genome sequencing (WGS) offers several advantages. The scientific or diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 167 publications
(156 citation statements)
references
References 89 publications
2
148
0
2
Order By: Relevance
“…When using diagnostic sequencing of ADA2 as the initial approach, caution is needed with interpretation of clinical significance of novel variants. The disease‐causing effect should not be extrapolated from variant‐level parameters, ie, allele frequency solely . Candidate variant segregation should comply with the disease recessive inheritance pattern.…”
Section: Diagnosismentioning
confidence: 99%
“…When using diagnostic sequencing of ADA2 as the initial approach, caution is needed with interpretation of clinical significance of novel variants. The disease‐causing effect should not be extrapolated from variant‐level parameters, ie, allele frequency solely . Candidate variant segregation should comply with the disease recessive inheritance pattern.…”
Section: Diagnosismentioning
confidence: 99%
“…These disease manifestations cause increased morbidity and mortality in patients, and treatment choices are often complex. With the increased accessibility of next‐generation sequencing (NGS), the rate of discovery of genetic causes for PID has increased exponentially in recent years, with now over 300 monogenic causes for PID described …”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, mutations and new genes are being identified that render the host susceptible to a specific pathogen [23]. Several genetic defects in the defence against TB have been identified [24].…”
Section: Discussionmentioning
confidence: 99%